PROPERTIES OF REFINED NATURAL ASPHALT BUTON (ASBUTON) as PAVEMENT MATERIALS - Furqon Affandi (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
There are two main types of bitumen i.e. those which occur naturally and those which are by product of the fractional distillation of petroleum. One type of natural bitumen is natural rock asphalt. There is a large reserve of natural rock asphalt in Buton Island-South East Sulawesi Province, Indonesia ; containing a bitumen content of 5% to 30% with an average bitumen content of 20% and remainder of the material is solid mineral matter, usually limestone or sandstone. The natural rock asphalt is known as Asbuton abbreviation of Asphalt Batu Buton i.e. Rock asphalt from Buton Island. The size of deposit has been variously estimated at up to 200 million tonnes. The deposit is therefore an important national resource with the potential to improve the properties of petroleum bitumen to carry the current and ever increasing traffic and axle loads in the future, reduce need imported bitumen and generated export income. To get a better quality Asbuton product, research and development has been ongoing. Available refining process has been developed. The refining process reduces the mineral content to produce Refined Asphalt Buton that has a bitumen content around 60% and new process has been recently developed produce a